ANALYSIS OF COMPENSATION SUITABILITY, INDIVIDUAL MORALITY, ETHICAL CULTURE, AND INTERNAL CONTROL ON FINANCIAL REPORTING FRAUD - Herawati, Herawati; Muslim, Resti Yulistia; Minovia, Arie Frinola; Karimi, Kasman; Deffira, Annissa (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This research aims to empirically analyses the compensation suitability, individual morality, ethical culture, and internal control on financial reporting fraud of accounting students in Padang. The sampling technique in this study is purposive sampling and data was collected by distributing questionnaire to accounting and finance students who had studied at least in the sixth semester on several university in Padang. This study uses the Gone Theory as a basis to examining the factors that cause fraudulent behavior towards financial statements. The Gone theory is a refinement of the triangle fraud theory, in which the two theories reveal the reasons a person commits an act of fraud. The Fraud Triangle Theory is a theory which explains three factors that causes of fraud that are Pressure, Opportunity, and Rationalization By using the multiple regression test, the results show that individual morality and internal control have a significant effect on financial reporting fraud, while suitability compensation and ethical culture have no significant effect on financial reporting fraud.Keywords: financial reporting fraud, compensation suitability, individual morality, ethicalculture, and internal control